Blue nevus with satellitosis: case report and literature review - Ana Helena Kalies Oliveira; Ana Flávia de Melo Cavalcanti Shiraishi; Bogdana Victoria Kadunc; Patrícia de Carvalho Sotero; Rafael Fantelli Stelini; Cínthia Mendes (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Blue nevus is a benign melanocytic lesion, typically asymptomatic and of unknown etiology. Many histological subtypes are recognized, the most commons being: common blue nevus, cellular blue nevus, and combined blue nevus. New rare variants have been described in the literature, with emphasis on eruptive blue nevus, plaque, agminate, linear, with satellitosis, disseminated, familial and targetoid. The diagnosis of blue nevus usually presents no difficulties, however, the presence of structures such as irregular edges or satellitosis, are highly suggestive of malignancy, and the differential diagnosis with malignant blue nevus and melanoma with peripheral spread should be considered. We report a case of blue nevus with satellitosis in a 15-year-old female patient.